EFEKTIVITAS KOMPRES HANGAT TERHADAP PENURUNAN NYERI PADA LANSIA YANG MENGALAMI REMATOID ARTHRITIS DI PANTI WREDHA MAJAPAHIT MOJOKERTO - Rahmawati, Ima; Ida Yanti, Nur (JURNAL KEPERAWATAN SEHAT, 2016)
Elderly is an age that many changes including changes in physical, social, and psychological. One of them is a change in the muskuloskletal and physical disorders as rheumatoid arthritis or joint disease. The disorder can cause interference of pain. Treatment for arthritis may include pharmacological therapies (drugs), and non-pharmacological, non-pharmacological measures for patients with arthritic pain include compresses, be it a cold compress and warm compress. Theresearch have purpose to know the effect of warm compresses about decrease pain in the elderly who have rheumatoid arthritis in Elderly Nursing Mojopahit Mojokerto. The design used was a pretest-posttest design. The population is the entire elderly who have rheumatoid arthritis with a sample of 15 respondents using purposive sampling techniques and data collection techniques observational pain scale before and after warm compresses. Data processing is done, in the test with the Wilcoxon signed rank test. The results showed significant results obtained α = 0.05 p = 0.001 which means that H0 is ignore H1 is accepted, which means there is the influence of a warm compress to the reduction of pain in older adults who have rheumatoid arthritis in Elderly Nursing Mojopahit Mojokerto. Warm compresses is one of the non-pharmacological measures to reduce pain, to provide information how and benefits of a warm compress and warm compress to train elderly so that the elderly can take action independently warm compresses.Keywords:Elderly, Pain, Warm Compres